2023
DOI: 10.1111/ppl.13924
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of intertracheid pit traits and climate effects among cycads

Abstract: Interconduit pit membranes, which are permeable regions in the primary cell wall that connect to adjacent conduits, play a crucial role in water relations and the movement of nutrients between xylem conduits. However, how pit membrane characteristics might influence water-carbon coupling remains poorly investigated in cycads. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Changes in pit traits can also influence the hydraulic safety and efficiency trade-off of plant xylem. A larger pit membrane area but lower pit density within individual cycad plants may provide higher hydraulic efficiency, which affects the hydraulic trade-off between safety and efficiency [97]. Although it has been shown that the structure of the pit affects the hydraulic trade-off, the exact mechanism underlying this is not clear.…”
Section: Tree Heightmentioning
confidence: 99%
“…Changes in pit traits can also influence the hydraulic safety and efficiency trade-off of plant xylem. A larger pit membrane area but lower pit density within individual cycad plants may provide higher hydraulic efficiency, which affects the hydraulic trade-off between safety and efficiency [97]. Although it has been shown that the structure of the pit affects the hydraulic trade-off, the exact mechanism underlying this is not clear.…”
Section: Tree Heightmentioning
confidence: 99%